2014
DOI: 10.1002/anie.201400420
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient Photocatalytic Fluorination of Unactivated CH Bonds

Abstract: Fluorination reactions are essential to modern medicinal chemistry, thus providing a means to block site-selective metabolic degradation of drugs and access radiotracers for positron emission tomography imaging. Despite current sophistication in fluorination reagents and processes, the fluorination of unactivated CH bonds remains a significant challenge. Reported herein is a convenient and economic process for direct fluorination of unactivated CH bonds that exploits the hydrogen abstracting ability of a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
130
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(140 citation statements)
references
References 36 publications
5
130
0
5
Order By: Relevance
“…The Inoue, 9 Tang, 10 and Hartwig 11 groups have also shown that N -oxyl radical and silver salts can catalyze or promote C–H fluorination. More recently, photolytic activation methods have also been reported by Britton, 12 Lectka, 8c and Tan 13 using decatungstate, 1,2,4,5-tetracyanobenzene (TCB), and anthraquinone (AQN) as the catalyst, respectively.…”
mentioning
confidence: 99%
“…The Inoue, 9 Tang, 10 and Hartwig 11 groups have also shown that N -oxyl radical and silver salts can catalyze or promote C–H fluorination. More recently, photolytic activation methods have also been reported by Britton, 12 Lectka, 8c and Tan 13 using decatungstate, 1,2,4,5-tetracyanobenzene (TCB), and anthraquinone (AQN) as the catalyst, respectively.…”
mentioning
confidence: 99%
“…28) [55]. The reaction was designed on the basis of the documented ability of 10 to abstract hydrogen atoms from saturated organic fragments upon irradiation with light [56].…”
Section: Fluorination Of C-h Bondsmentioning
confidence: 99%
“…An example is sclareolide: acetophenone 9 (80%/16 turnovers), anthraquinone 10 (77%/39 turnovers), 1,2,4,5-tetracyanobenzene 7 (61%/6.1 turnovers), and TBADT 8 (68%/34 turnovers) all produced mixtures of monofluorinated products in moderate to high yields as compared to the low result observed for the uranium system (26%/26 turnovers, Table 3, Entry 11). Similarly, acetal and ether functional groups are incompatible with the uranyl system, with the dioxolane derived from condensing cyclopentanone with ethylene glycol providing even less reactivity than the parent ketone (Table 3, Entry 12) and tert -butyl methyl ether not producing any fluorinated product.…”
mentioning
confidence: 96%
“…Indeed, the recent reports from Lectka, 7 Britton, 8 Chen, 9 and Tan 10 suggests that, despite progress, this transformation is not yet a solved problem. With some exceptions, 11,12,13 recent strategies for selectively fluorinating C sp3 –H bonds have largely recruited photo-hydrogen atom abstraction (HAT) catalysts (denoted [cat]), such as acetophenone, anthraquinone, 1,2,4,5-tetracyanobenzene, and tetra- n -butylammonium decatungstate (TBADT, Figure 1), to generate a carbon-centered radical.…”
mentioning
confidence: 99%